Development of Trichoderma Formulation and Application to Control Durian Anthracnose Disease - Sutthisa, Waraporn; Popranom, Aranya; Taddeetrakool, Atchara; Khankhum, Surasak (Trends in Sciences, 2023)
Anthracnose is a plant fungal disease that damages both quantitative and qualitative crop yields. Biological control of plant disease is an alternative method enabling reduced use of chemicals. The objective of this research was to develop a formulation of Trichoderma for controlling plant anthracnose disease. The efficacy of T. asperellum MSU007 in controlling Colletotrichum sp. by dual culture technique showed that T. asperellum MSU007 was able to inhibit the mycelium growth of Colletotrichum sp. with 50.76 - 74.85 % inhibition. Three formulations of T. asperellum MSU007 were developed. The viability of T. asperellum MSU007 in the formulation after drying at 45 °C showed that the viabilities of formulation 2 and 3 were not significantly different at 5.26×108 and 5.30×108 cfu/g, respectively, while that of formulation 1, the viability of T. asperellum MSU007 was reduced to 3.73×106 cfu/g. After storage at room temperature for 30 days, formulations 2 and 3 did not result in significantly different viability of T. asperellum MSU007 at 4.40×108 and 4.90×108 cfu/g, respectively, and after 90 days of storage at room temperature, it was found that only formulation 3 did not decrease T. asperellum MSU007 viability at 4.33×108 cfu/g. The efficacy of Trichoderma bioproduct in inhibiting anthracnose pathogens on durian leaves was tested. It was found that spraying formulation 3 after inoculation of Colletotrichum sp. resulted in the least anthracnose severity at 15.67 ± 4.04 %, which was significantly different from other treatments including the use of carbendazim. However, it is necessary to further study the efficacy of Trichoderma formulation in the inhibition of durian anthracnose pathogens in field conditions in order to be able to use this bioproduct in future disease control. HIGHLIGHTS This research developed an effective Trichoderma bioproduct to control the durian anthracnose causative agent Colletotrichum spp. which has sufficient potential to be developed and applied in the control of this disease, replacing the use of chemicals in the future. GRAPHICAL ABSTRACT